Maktkontinuitet i munningen av Trondheimsfjorden - Birgitta Berglund; Thyra Solem (Heimen)
Abstract The Trondheimsfjord runs from the Norwegian west coast far to the east, from where routes along the rivers lead to the Gulf of Bothnia. Continuity in power and prosperity at the mouth of the fiord is discussed, with the starting point in material culture from ca. 800 BC–1200 AD. Ørlandet at the mouth of the fiord is important, and the vicarage at Veklem there is used as the main example. There we find the perhaps biggest grave mound in Sør-Trøndelag County and a stone church with its roots in 1000–1300 AD. Archeological excavations in the decades around the year 2000 have revealed remains from 800–1200 AD there. The first pollen analysis combined with macrofossil investigations to shed light over a prehistoric farm in Trøndelag is done at Veklem.